Repeating earthquakes record fault weakening and healing in areas of megathrust postseismic slip - Chaves, Esteban (2020)
Repeating earthquakes (REs) rupture the same fault patches at different times allowing temporal variations in the mechanical behavior of specific areas of the fault to be interrogated over the earthquake cycle. We study REs that reveal fault weakening after a large megathrust earthquake in Costa Rica, followed by fault recovery. We find shorter RE recurrence intervals and larger slip areas immediately following the mainshock that both gradually return to pre-earthquake values. RE seismic moments remain nearly constant throughout the earthquake cycle. This implies a balance between fault weakening (reducing slip) and transient embrittlement (increasing rupture area by converting regions from aseismic to seismic slip), induced by the increased loading rate following the mainshock. This interpretation is consistent with positive, negative, and constant moment versus RE recurrence interval trends reported in other studies following large earthquakes and with experimental work showing slip amplitudes and stress drop decrease with loading rate.